2015
DOI: 10.2987/14-6466r
|View full text |Cite
|
Sign up to set email alerts
|

The Sabethines of Northern Andean Coffee-Growing Regions of Colombia

Abstract: Sampling for sabethine mosquitoes occurred intermittently from September 2007 to April 2013 in 17 municipalities, located in 5 departments (divisions) in the northern Andean coffee-growing regions of Colombia. Of the 9 genera within the Sabethini tribe known to occur in the Neotropical region, 6 were encountered including 15 species: Jonhbelkinia ulopus, Limatus durhamii, Sabethes ignotus, Sa. luxodens, Sa. undosus, Shannoniana fluviatilis, Trichoprosopon compressum, Tr. digitatum, Tr. evansae, Tr. pallidivent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…The climax species Li . durhamii had two peaks as well, a very high one at high forest cover, supported by Suaza-Vasco 41 , and another with low abundance at intermediate/low forest cover. Additionally, we found five species that can be considered disturbance-generalists, because they had at least two peaks of equal abundances in different forest disturbance categories.…”
Section: Discussionmentioning
confidence: 81%
“…The climax species Li . durhamii had two peaks as well, a very high one at high forest cover, supported by Suaza-Vasco 41 , and another with low abundance at intermediate/low forest cover. Additionally, we found five species that can be considered disturbance-generalists, because they had at least two peaks of equal abundances in different forest disturbance categories.…”
Section: Discussionmentioning
confidence: 81%
“…However, a previous study conducted in a coffee-growing region of Colombia reported larvae of Trichoprosopon sp. in a Xanthosoma leaf axil (Suaza-Vasco et al ., 2015). Moreover, at least three species of Trichoprosopon are present in the Jardin and Jericó municipalities, including two species of the Pallidiventer Complex, Tr.…”
Section: Discussionmentioning
confidence: 99%
“…sp. B (Barajas et al ., 2013; Suaza-Vasco et al ., 2015). Therefore, we hypothesize that the two cox1 sequences from Trichoprosopon adult females collected in Jardín at 2,253 m are Tr.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in Jardín municipality (ANT), nine species of the tribe Sabethini were collected in bromeliads and leaf axils of Xanthosoma in a forest environment between 2,245–2,515 m, whereas other Sabethini species were found on a different Xanthosoma sp. in an urban setting at 2,002 m in Jericó municipality (ANT), Colombia (Suaza‐Vasco et al ).…”
Section: Introductionmentioning
confidence: 99%